2019
DOI: 10.3390/ncrna5010028
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Shuttle from Cell-To-Cell by Exosomes and Its Impact in Cancer

Abstract: The identification of exosomes, their link to multivesicular bodies and their potential role as a messenger vehicle between cancer and healthy cells opens up a new approach to the study of intercellular signaling. Furthermore, the fact that their main cargo is likely to be microRNAs (miRNAs) provides the possibility of the transfer of such molecules to control activities in the recipient cells. This review concerns a brief overview of the biogenesis of both exosomes and miRNAs together with the movement of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 156 publications
1
79
0
Order By: Relevance
“…And among various prognostic, diagnostic, and therapeutic biomarkers, miRNA has emerged as a powerful biomarker for the detection, treatment, and monitoring of response to therapy in cancer . Especially, exosomes provide shuttle cargos for transferring microRNA from cell‐to‐cell and leading to abnormal expression of genes, resulting in tumorigenesis and cancer development . For example, natural killer‐derived exosomal miR‐186 inhibits neuroblastoma growth and immune escape .…”
Section: Disccussionmentioning
confidence: 99%
“…And among various prognostic, diagnostic, and therapeutic biomarkers, miRNA has emerged as a powerful biomarker for the detection, treatment, and monitoring of response to therapy in cancer . Especially, exosomes provide shuttle cargos for transferring microRNA from cell‐to‐cell and leading to abnormal expression of genes, resulting in tumorigenesis and cancer development . For example, natural killer‐derived exosomal miR‐186 inhibits neuroblastoma growth and immune escape .…”
Section: Disccussionmentioning
confidence: 99%
“…The allelic loss, copy number aberrations, mutations, and methylations of CSMD1 have been detected in various malignant tumours such as head and neck tumor, colorectal cancers, liver cancer, and so on [5][6][7][8][9][10][11][12][13][14][15][16]. Besides, it has been proved that the change of microRNA expression and dysfunction play an important role in tumorigenesis and metastasis by regulating target genes and pathways, subsequently resulting in the alteration of proliferation, differentiation, apoptosis, invasion and metastasis of tumor cells [17][18][19]. Therefore, the molecular mechanism underlying the microRNAs-driven deregulation of CSMD1 contributing to GC metastases need to be urgently unraveled.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA is a small single-stranded non-coding RNA, that is a post-transcriptional negative regulator that binds completely or partly to the complementary sites in the 3′-untranslated region (3′UTR) of target mRNAs [17][18][19]. Accumulating evidence has shown that miRNAs can modulate tumor growth, metastasis, and progression by regulating multiple target genes [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it will be interesting to elucidate how a released miRNA is able to specifically reach its cellular target within the complex tumor microenvironment. In this situation, a more complex ECmiRNAs uptake system than the random endocytosis, micropinocytosis, or phagocytosis should be hypothesized [205,206]. The expression of specific molecules on the surface of membrane vesicles, such as glycolipids or lipoproteins, could facilitate the binding to specific receptors on the membrane of the targeted cells.…”
Section: Discussionmentioning
confidence: 99%